Case Report: Novel endoscopic characteristics of early-stage autoimmune gastritis from two cases: the fog is lifting - Song, Yiming; Yan, Jianing (Frontiers in Immunology, 2025)
With the development of research, the clinical characteristics of autoimmune gastritis (AIG) have become much clearer. However, due to its occult endoscopic appearance, it remains difficult to diagnose early, including ultra-early AIG. More cases and typical clinical characteristics should be proposed and concluded to guide clinicians. Hence, we selected two novel cases of early AIG and summarized their common endoscopic features in order to improve diagnostic ability. We found two interesting features for early AIG: 1) deep reticular blood vessels in the lower part of the cardia mucosa and 2) various manifestations of crypt opening shown on narrow-band imaging (NBI) magnification, such as dilation, pinhole-like, shrinkage, and disappearance. Future studies promise even more progress with the hope that these features can be found in more cases.